Pandian tamil journal of temple studies - Pandian educational trust (Pandian educational trust, 2020)
"Pandian Tamil Journal of Temple Studies aims to bring down Academic Research to promote research support for the academicians and scholars in the field of Temple Studies... The purpose of this peer-reviewed journal is to explore the origins, design, worship, spiritual philosophy, doctrines of the temples, architecture, temple work of the Tamils, charity, music and musical instruments, folk music, temple folk, the spiritual hymns of the sect, Tamil Bhakthi literature, Bhakthi literature in general to Hindu religion from any language of India and Abroad and universal temple art."-- Publisher's website (Pandian Educational Trust).
Keywords: Hindu temples : India : Periodicals; Hindu temples : Sri Lanka : Periodicals; Temples : India : Periodicals; Temples : Sri Lanka : Periodicals; Pandyas : Periodicals; Hindu rock-cut temples : India : Periodicals; Hindu rock-cut temples : Sri Lanka : Periodicals; Tamil (Indic people) : Religion : Periodicals